엑스선골밀도측정기의 기술문서 작성을 위한 가이드라인 개발 연구 - 이승열(Seung Youl Lee); 김재량(Jae Ryang Kim); 김은림(Eun Rim Kim); 이준호(Jun ho Lee); 이창형(Chang Hyung Lee); 박창원(Chang Won Park) (방사선기술과학, 2016)
The market size of the bone absorptiometric X-ray system and the number of its approval by Ministry of Food and Drug Safety (MFDS) has annually increased, with a trend of increasing aging population and osteoporosis patients. For approval of manufactured or imported medical devices in Republic of Korea, it is required to submit its technical document. Therefore, it is need to develop the technical document guideline for the bone absorptiometric X-ray system for manufacturers, importers and reviewers. First of all, the technical documents which were already approved were examined and analyzed through MFDS approval administration system. Second, safety and performance test standards and methods that match international standards were drawn after conducting survey of the market status and the technology development trend for it, with examination and analysis of applicable domestic and overseas standards. Third, by operating industry-research-government cooperation, the guideline draft on writing technical document for the bone absorptiometric X-ray system was discussed, collecting their opinion. As a result, it is suitable to international and domestic condition, includes test evaluation methods and offer various information with appropriate examples to civil petitioner, when they write the technical documents. 최근 인구 고령화에 따른 골다공증 환자의 증가 및 의료기기 시장의 성장으로 인해 엑스선골밀도측정기 시장이 커지고 있으며, 이에 따른 의료기기 허가 심사건수가 증가하고 있다. 의료기기 기술문서는 의료기기의 허가 심사 시 가장 기본이 되는 문서로 필수 제출 첨부자료 중 하나이다. 기술문서는 의료기기 관련 법령 및 고시에 그 근거를 두고 있으며, 의료기기 전반적인 항목을 기술해야하는 만큼 작성자의 전문성이 필요한 항목이다. 하지만 최근 부정확한 작성의 증가로 인한 심사자들의 업무부담이 증가되고 있어 민원 처리 효율이 저하되고 있다. 특히 엑스선골밀도측정기의 경우 식품의약품안전처 기준규격이 없어, 의료기기 제조/수입업체 등에서 시험항목을 설정하는 데 많은 어려움을 겪고 있다. 따라서 본 연구에서는 개선된 제도가 반영된, 엑스선골밀도측정기 기술문서 작성 가이드라인 개발을 위해 첫째, 개선된 제도 운영에 대한 조사, 품목별 의료기기의 제도 적용에 따른 문서 작성 방법 검토, 기 허가된 품목에 대한 허가 및 기술문서 검토를 완료하였다. 둘째, 품목별 시장현황 조사, 적용 가능한 국내 외 규격을 조사 분석하여 품목별 국제조화된 안전성 및 성능평가 시험기준 및 방법을 도출하였다. 마지막으로, 산 연 관 전문가협의체 논의를 거쳐 기술문서 작성 가이드라인(안)을 최종 도출하였다.